PERANCANGAN MEDIA PEMBELAJARAN AUTOCAD BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) PADA MATA PELAJARAN PRODUKTIF TEKNIK GAMBAR BANGUNAN DALAM BENTUK CAKRAM OPTIK (Jurnal Pensil)
The design of this innovative work does in order to enhance to quality of learning for the students and create some variations in learning especially in studying AutoCAD. The implementation time of designing this work starts from December 1st, 2011 until December 31st, 2011.